Severe acute respiratory syndrome coronavirus-2 antibody prevalence in people with and without HIV in rural Western Kenya, January to March 2020. (15th November 2021) - Crowell, Trevor A.; Daud, Ibrahim I.; Maswai, Jonah; Owuoth, John; Sing'oei, Valentine; Imbach, Michelle; Dear, Nicole; Sawe, Fred; Eller, Leigh Anne; Polyak, Christina S.; Ake, Julie A.
Abstract : Supplemental Digital Content is available in the text Abstract : : Among 582 participants in Western Kenya who were retrospectively tested from January through March 2020, 19 (3.3%) had detectable SARS-CoV-2 antibodies. The prevalence of detectable SARS-CoV-2 antibodies was similar between participants with and without HIV (3.1% vs. 4%, P = 0.68). One participant reported a cough in the preceding week but others denied symptoms. These may represent cross-reactivity or asymptomatic infections that predated the first reported COVID-19 cases in Kenya.